2020
DOI: 10.1002/aisy.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Controlled Colloidal Assembly of Soft Microrobotic Artificial Muscle

Abstract: Herein, a methodology for the directed self‐assembly of untethered microactuators and soft robotic microdevices from nanoscale building blocks is presented. The building block is a multifunctional stimuli‐responsive nanoactuator that consists of a magnetized gold nanorod encapsulated by a thermoresponsive hydrogel. The metallic core serves as a photonic nanoheater that transduces thermal energy from near‐infrared (NIR) light and a magnetic nanomotor that generates motion while driven by magnetic fields. Rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…An alternative solution is to push the printing concept to the next level. We have recently shown that the nOMAs could be assembled on-demand by harnessing thermocapillary flows (Parreira et al, 2020 ). Thus, it is conceivable that the whole machine can be manufactured in situ using direct laser writing.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative solution is to push the printing concept to the next level. We have recently shown that the nOMAs could be assembled on-demand by harnessing thermocapillary flows (Parreira et al, 2020 ). Thus, it is conceivable that the whole machine can be manufactured in situ using direct laser writing.…”
Section: Discussionmentioning
confidence: 99%
“…Janus particles are asymmetrical, as seen in Figure 5d, allowing for self-assembly to enable functions which are not possible for the individual components. Janus particles have potential microfluidic and biomedical applications including sensing, catalysis, imaging, and drug delivery [119]. The particles can be manipulated and guided using various methods including light, magnetism, and pH [120].…”
Section: Janus Particlesmentioning
confidence: 99%
“…[135] The optical gradient force of a focused laser has been used to generate light traps that can assemble microparticles into welldefined micropatterns. [136][137][138][139] Optical traps were generated by creating an interfering pattern between an annular-shaped laser and a reference beam. Nearby objects were trapped inside the spiral interference pattern.…”
Section: Optical Reversible Dynamic Assemblymentioning
confidence: 99%